ANALISIS KEPUASAN PENGGUNA FACEBOOK TERHADAP LAYANAN DAN KONTEN YANG TERSEDIA - Astika Ramadani; Emy L. Tatuhey (ADISAM PUBLISHER, 2025)
This research aims to analyze Facebook user satisfaction with the services and content available in Jayapura, a crucial issue given Facebook's dominant role as a communication and interaction platform in today's digital era. This study adopts the End-User Computing Satisfaction (EUCS) model as its primary measurement framework, encompassing five critical dimensions: content, accuracy, format, ease of use, and timeliness. A quantitative research method was employed, with data collected through questionnaires distributed to 100 Facebook users in Jayapura, analyzed using a 5-point Likert scale. Validity test results indicate that all 14 questionnaire items are valid, with rcalculated​ values greater than rtable​ (0.245). The internal consistency of the instrument also proved reliable, evidenced by a Cronbach's Alpha value of 0.611491, categorized as acceptable. Based on the analysis of average scores per dimension, users demonstrated neutral to satisfied levels of satisfaction regarding Content (average 3.09), Ease of Use (average 2.99), and Timeliness (average 2.98). However, the Accuracy (average 2.91) and Format (average 2.97) dimensions tended towards a neutral level, with information accuracy being an area requiring further attention. This research is expected to provide valuable insights for Facebook developers to enhance platform quality to meet user expectations and maintain its relevance amidst fierce social media competition.